Development and testing of the phytoplankton biological integrity index (P-IBI) in dry and wet seasons for Lake Gehu. (October 2021) - Zhu, Han; Hu, Xiao-Dong; Wu, Pei-Pei; Chen, Wen-Meng; Wu, Su-Shu; Li, Zhi-Qing; Zhu, Liang; Xi, Yi-Long; Huang, Rui
Graphical abstract: Highlights: The water ecological health assessment results were "moderate" in dry and wet periods by P-IBI. The proposed P-IBI was closely correlated with the water quality environmental factor. The stability of the P-IBI during the dry season is better than wet season. Abstract: Taking Lake Gehu located in the Yangtze River Delta as the research object, the phytoplankton community and environmental variables at 18 sampling sites in Lake Gehu were monitored and investigated during the dry season (March) and the wet season (July) of 2020. On this basis, the phytoplankton biological integrity index (P-IBI) was established during dry and wet periods, and the health of the lake water ecosystem was evaluated. The results showed that the P-IBI in dry and wet periods was consistent throughout Lake Gehu, and the overall water ecological health assessment results were "moderate". To test the stability of the P-IBI, the relationships between the P-IBI, its constituent parameters and a single water quality environmental factor were analyzed through redundancy analysis (RDA). The results showed that total nitrogen, the hypermanganate index, chlorophyll a, dissolved oxygen, ammonia nitrogen, and transparency were highly correlated with the P-IBI system. Comparing the composition of the P-IBI during dry and wet periods and the relationships between the P-IBI system and water quality factors in the two hydrological periods, it was found that the parameters of the P-IBI system differed greatly between the dry and wet periods. The number of significantly related water quality factors in the dry period was greater than that in the wet period, and the two-axis characteristic values, the correlations between the P-IBI system and the water quality factors, and the cumulative percentage of the dry period were higher than those in the wet period. In conclusion, the P-IBI exhibits temporal variation between hydrological periods, and the stability of the P-IBI evaluation system during the dry season is significantly better than that during the wet season.